The Effect of Using TAPPS (Thinking Aloud Pair Problem Solving) Method on Learning Outcomes of Class X Science Fiqh Material at Sabilillah High School Malang - Taufik Rizki Sista; Abu Darda; Lusiana Hadi Febrianty (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2023)
Less attractive learning practices always cause problems in student academic achievement results. Especially in religious studies, which in general are teachings with a pattern of delivering lectures. Fiqh subject matter is one of the Islamic subjects that uses teacher creativity in learning to attract students' interest and attention. This study aims to determine the influence of the use of the TAPPS (Thinking Aloud Pair Problem Solving) method on the academic performance of class X Fiqh subject matter science at Sabilillah High School Malang. The research method used is quantitative with an experimental approach (True experimental design). The data analysis technique used is Mann Whitney's U-test because the data obtained is not qualified to be tested with a parametric approach. The results of the data analysis showed that the output on the Mann Whitney U Significance test was 0.000 < 0.05 which means that Ha was accepted and Ho was rejected. It can be concluded that the TAPPS (Thinking Aloud Pair Problem Solving) method has an effect on the academic performance of students of class X Fiqh subject matter at Sabilillah Malang High School.